ASSESSMENT OF IRON DEFICIENCY IN PREGNANT WOMEN BY DETERMINING IRON STATUS - Raza, Nuzhat; Sarwar, Iram; Munazza, Bibi; Ayub, Muhammad; Suleman, Muhammad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Pregnant women constitute a high risk group for iron deficiency. Maternal iron deficiency and particularly iron deficiency anaemia may be associated with detrimental effects on maternal and infant function and particularly with a higher risk of preterm delivery and delivery of low birth weight neonates. Objective of this study was to assess and compare the iron status of normal healthy non-pregnant women with that of pregnant women of Hazara Division. Methods: This study was conducted at Faculty of Health Sciences, Hazara University, and Ayub Medical College, Abbottabad from 1st March to 31st August 2006. Altogether 120 women, 90 pregnant at various stages of pregnancy and 30 non-pregnant women as control group were included in this study by convenience sampling. Their iron status was assessed by determination of haemoglobin (Hb), Serum ferritin, Serum-iron, Total Iron Binding Capacity (TIBC), Unsaturated Iron Binding Capacity (UIBC), and Percentage saturation of transferrin. Data generated on these variables were subjected to ANOVA and correlation analysis. Results: The salient finding of this study is a significant decrease in Hb, Serum ferritin, Serum iron, percentage saturation of transferrin and a significant increase in values of TIBC and a pronounced increase in UIBC in 2nd and 3rd trimester compared to 1st trimester in iron deficient pregnant women. The mean values of Hb, SF, and Fe/TIBC% were significantly lower in the cases than in the control and significantly higher values of TIBC and UIBC were observed in the cases compared to controls. Significant correlations were observed for TIBC, UIBC and Fe/TIBC% against serum iron in different trimesters of pregnancy. Conclusion: A high percentage of the pregnant women are iron deficient due to factors such as high parity, poor dietary habits and socioeconomic status. Keywords: Iron-deficiency, pregnancy, Anaemia, Ferritin, TIBC, UIBC, Transferrin